A diagnostic dilemma in an infant: a case of infantile cortical hyperostosis overlapping with chronic recurrent multifocal osteomyelitis - Raut, Dinkar; Walhekar, Sagar Yamnaji; M. M., Meghana; Misra, Anjini (International Journal of Contemporary Pediatrics, 2025)
Caffey’s disease, first described by Caffey and Silverman in 1945 is also known as infantile cortical hyperostosis (ICH), is a condition that affects infants and is mostly self-limiting. Presenting with painful soft tissue swellings, fever and irritability, it is characterized by cortical thickening of the underlying bones. Its clinical presentation can mimic infectious osteomyelitis, leading to diagnostic challenges. We report a case of a 2-month-old male infant with multifocal bony involvement and genetic findings suggestive of chronic recurrent multifocal osteomyelitis (CRMO), but with clinical features strongly favouring Caffey disease. This case highlights the overlap between autoinflammatory bone disorders in infancy and emphasizes the importance of integrating clinical, radiological, and genetic findings to arrive at an accurate diagnosis. This case is reported to get the awareness of the paediatricians about the disease, its existence in our population, presentation, and important differential diagnoses and management.